The Demand Cor International Reserves and their Opportunity Cost. (IMF Working Papers; Working Paper, 1988)
An empirical study that shows that countries' reserve holdings are sensitive to the rates at which they can borrow on international financial markets, this analysis confirms the view that holding major currencies as reserve assets has costs that are frequently unrecognized. Between 1978-82 for 24 sample countries, and between 1978-86 for the same sample less those countries with debt-servicing difficulties, international borrowing costs were found to be a highly significant determinant of reserve holdings-particularly before 1982 for the group with debt difficulties.